(untitled) (Jurnal Bahasa, 2018)
Empirical studies of Malay phonology as used by Chinese speakers (ChinMalay) are scarce. Contributing factors, such as the medium of instruction used in schools, are under-explored. The present cross-sectional study aims to investigate the consonant and vowel production of Malay by 90 adult Chinese speakers. Specifically, it aims to compare the pronunciation of subjects who had attended primary schools (Sekolah Kebangsaan/Sekolah Jenis Kebangsaan Cina) followed by secondary schools (Sekolah Menengah Kebangsaan/Sekolah Tinggi Persendirian Cina). These subjects have been exposed to three types of medium of instruction respectively. : 1. Malay-Malay. 2. Mandarin-Malay. 3. Mandarin-Mandarin. All subjects were tested using the Malay Phonological Test (picture-naming) devised for this study. Qualitative analysis reveals the following errors: deviation of -ɲ & -r; aspiration of plosives -p & affricate-tʃ and final consonant deletion -h & -l. Statistical analysis shows significant differences only for initial -tʃ and final -h & -l where the Malay-Malay group achieved higher scores than the other two groups. Influences from Mandarin and English, and speaking style both contributed to ChinMalay phonology. Keywords: Chinese speakers, Chinese Malay (ChinMalay) phonology, consonant production, vowel production, speech production in Malay, school language medium, language input, speaking style, Malay phonology test